ALCOHOL DETECTOR - Karale Ashwini; Sathe Priti; Sonawane Pratiksha (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Alcohol detector is a device to measure blood alcohol content (BAC) from breath sample. In most countries 0.08 grams of alcohol per 100 mL of blood (BAC 0.08) is set as the legal limit beyond which the person or driver is considered to be legally drunk.Technically alcoholism is determined by the driver’s blood alcohol level called the ‘blood alcohol concentration’ (BAC), which indicates the degree of intoxication.Blood alcohol levels may be evaluated by using the GAS SENSOR. By gas sensor we are able to sense carbon dioxide, ammonia, nitrogen etc